Practical Site Reliability Engineering Automate the process of designing, developing, and delivering highly reliable apps and services with SRE - Chelliah, Pethuru Raj (Packt Publishing Limited, 2018)
bCreate, deploy, and manage applications at scale using SRE principles/b h4Key Features/h4 ulliBuild and run highly available, scalable, and secure software /li liExplore abstract SRE in a simplified and streamlined way /li liEnhance the reliability of cloud environments through SRE enhancements /li /ul h4Book Description/h4 Site reliability engineering (SRE) is being touted as the most competent paradigm in establishing and ensuring next-generation high-quality software solutions. This book starts by introducing you to the SRE paradigm and covers the need for highly reliable IT platforms and infrastructures. As you make your way through the next set of chapters, you will learn to develop microservices using Spring Boot and make use of RESTful frameworks. You will also learn about GitHub for deployment, containerization, and Docker containers.